Integrative stemness- and EMT-related gene signatures associated with prognosis and the immune microenvironment in lung adenocarcinoma - Fei Lu; Lan Li; Li Wang; Sisong Shu; Jingyan Gao; Li Chang; Hui Yu; Wenhui Li; Yaoxiong Xia (Discover Oncology)
Abstract This study aims to comprehensively analyze the genetic characteristics and prognostic value of stemness- and epithelial-mesenchymal transformation (EMT)-related gene signatures in lung adenocarcinoma (LUAD). The RNA-sequencing transcriptome profiling data and corresponding clinical information of LUAD were procured from TCGA-LUAD and GEO datasets. After screening, we first obtained 1488 stemness- and EMT-related genes. Then 304 hub genes were obtained via WGCNA, of which 52 genes were established to be prognosis-related hub genes. Thereafter, a prognostic model containing 11 genes (ANGPTL4, CCL20, ENO1, FGF2, LGR4, PIM2, S100P, SATB2, SHOX2, ZNF322, and CFTR) was constructed. We demonstrated that a higher risk score was an independent negative prognostic factor in LUAD patients. A nomogram was further constructed to better predict the survival of LUAD patients. More importantly, we found that the low-risk group has a more favorable anti-tumor immune microenvironment and may benefit more from immunotherapy. We finally noticed that the high-risk group was more sensitive to most drugs including drugs commonly used to treat LUAD patients. In conclusion, this study has summarized the alterations and prognostic role of stemness- and EMT-related gene signatures in LUAD and constructed a prognostic model to accurately and stably predict survival and guide individualized treatment decisions.